O real do feminino em Hamlet, Macbeth e Rei Lear: considerações sobre o suicídio em Lacan - Ferretti, Mariana Galletti (2015)
Building on the lacanian concept of the real that which is beyond the signifier and the order of the symbolic , this study intends to articulate such a concept to the renowned shakespearian tragedies of Hamlet, Macbethand King Lear. It examines in what measure the study on the suicides, present in these shakespearian works, enables the articulation between the concepts of the real and that of the passage to the act. To Lacan, suicide can be a sort of passage to the act that bears, in its self, a relation to the real. Since these suicides are perpetrated by women, it is most relevant that we focus on the matter of the femininity in psychoanalysis, a subject which, in turn, can provide us with important resources to help us think about the topic. To Lacan there is no complementarity, exactly because women can t be represented in a aggregation; it is this non-existing relation between sexes, one of the fundamental lacanian psychoanalytic principles, that makes this analytic practice a Other treatment. Since it is aiming for the real, not femininity, a woman s analytic process has the potency to enable her to exist not as A but as one woman